Upaya Peningkatan Pengetahuan Remaja Putri Tentang Personal Hygiene Saat Menstruasi Melalui Metode Lecturing di SMPN 18 Surakarta - Sugiarti, Ika; Permana Putra, Firdy Rama; Afriyanto, Dzul Fahmi; Salsabila, Muna Maimunah (Jurnal Abdimas Kesehatan (JAK), 2024)
Based on GLOBOCAN estimates in 2018, cervical cancer is ranked second in cancer incidence with 32,469 new cases and ranks third as a cause of death from cancer with 18,729 deaths in Indonesia. Hygiene during menstruation plays an essential role in a person's health status, including avoiding disorders in the function of the reproductive organs. During menstruation, blood vessels in the uterus are very easily infected. Therefore, genital hygiene must be maintained because germs can quickly enter and cause reproductive tract diseases. Consequently, it is necessary to increase knowledge about Surakarta and personal hygiene among adolescents, especially adolescents at SMPN 18 Surakarta City, many of whom still do not know the dangers of poor personal hygiene during menstruation. This community service aims to provide information about personal hygiene during menstruation to SMPN 18 Surakarta City students. The community service method uses lecturing, intervention using powerpoint, discussion and question and answer. This community service activity is done through socialization with PowerPoint presentations to 16 SMPN 18 Surakarta students. There is an increase in knowledge related to personal hygiene during menstruation using the lecturing method, with the pre-test category of good knowledge only 11 students; after the intervention of information exposure, the post-test results showed that good knowledge increased to 16 students. There is an increase in students' knowledge about personal hygiene during menstruation using the lecturing method.